Journal writing: a tool to help develop student voice - Боскин, Т. Б. (My University, 2016)
This articleexplores experience with a journal writing activity held in English as a Foreign Language (EFL) classroom and focuses on its role indevelopment of student voice. The aim was to explore journal writing as a means to help develop students’ voices,which is considered here as representation of learners’ own ideas, opinions, and knowledge. Thisis of great importance for students, sincethey are to be demonstrated for the successful passing international standardized tests.Moreover, the development of a learner’s voice is an important factor, not only for their personal growth, but also it tends to contribute to create positive and warm atmosphere in the classroom that lead to general academic improvement. In theresearch, ninth grade students in a specialized secondary school were assigned to write entries in the journals during the lessons on particular topics. Later, the journals were collected and analyzed through specifically constructed schemes, including those that are based on a revised Bloom’s Taxonomy. The results of the study revealed the development of students’ voices in a number of different way including evaluating, creativity, and formatting. This article aims to describe the most interesting, in the author’s opinion, part of the findings – creativity aspect. Eventually, there are some practical recommendations on how journal writing activity may be better incorporated in EFL classroom.
Keywords: journal writing activity; students’ voices, writing to learn; evaluation; creativity